2015
DOI: 10.11114/ijsss.v3i6.1170
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of EFL Jordanian University Instructors of the Process of Teaching/Learning the Translation of Idioms

Abstract: The study aimed at investigating the perceptions of EFL Jordanian University instructors of the process of teaching/learning the translation of idioms. The participants of the study were six M.A translation instructors at the University of Jordan and Yarmouk University who were selected purposefully. The total number of the instructors was 6. The instrument of the study was an interview with the translation instructors. The instructors indicated that teaching students how to translate idioms is not an easy tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Despite their common practice and popularity in other research settings, studies on idiomatic translation in the Arab setting, in general, and the Saudi context, in particular, have been scarce (e.g., Salamah, 2012;Al-Assaf, 2019;Alrishan and Smadi, 2015;Salamah, 2012). For instance, Salamah (2012) investigated difficulties associated with idiomatic comprehension and translation.…”
Section: Difficulties Of Processing and Translating Idioms And Cultur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their common practice and popularity in other research settings, studies on idiomatic translation in the Arab setting, in general, and the Saudi context, in particular, have been scarce (e.g., Salamah, 2012;Al-Assaf, 2019;Alrishan and Smadi, 2015;Salamah, 2012). For instance, Salamah (2012) investigated difficulties associated with idiomatic comprehension and translation.…”
Section: Difficulties Of Processing and Translating Idioms And Cultur...mentioning
confidence: 99%
“…In another study, Alrishan and Smadi (2015) investigated translation strategies used by Jordanian EFL university graduate students when translating English idioms into Arabic. With 90 MA Translation students being tasked to complete a translation test containing 16 idioms from different categories, the researchers found that the participants encountered several problems when processing and translating English idiomatic expressions into Arabic.…”
Section: Difficulties Of Processing and Translating Idioms And Cultur...mentioning
confidence: 99%
“…In addition, this research has been carried out by previous by Arono & Nadrah (2019) regarding "Difficulties of Students Translating English Texts" which states that students' difficulties in translating are lack of vocabulary, difficulty translating Islamic texts, literary works, and grammar problems. Meanwhile, another difficulty stated by Baker (1992) in Alrishan (2015) is the use of idioms that have similar forms and meanings in different contexts from the target language. Based on the explanation above, this research is very important to find out the difficulties of students in translating texts, as well as the causes of students' difficulties in translating English texts to Indonesian texts.…”
Section: Difficulties Of Translationmentioning
confidence: 99%
“…English idioms are used frequently in everyday situations, and therefore they need to be considered and used by teachers and lecturers in EFL classes. So, the training of EFL learners on using English idioms as lexical chunks has to go beyond the simple word-by-word comprehension strategy and integrating figurative meaning idioms are very common in both written and spoken language (Alrishan(2015); Chen& Lai( 2013); Pimenova (2011); Bagheri& Fazel (2010); Boers (2008); Brown (2001); Nunan (2003); Burke, 1998). Examples of some English idioms are, e.g.…”
Section: English Idioms Collocations and Phrasal Verbsmentioning
confidence: 99%